Condensed Matter Nuclear Science : (World Scientific, 2006)
This volume is a collection of papers from the Tenth International Conference on Cold Fusion attended by most of the important groups around the world that are active in the field. New results are presented in the area of excess heat production, including observations of excess heat, correlation of excess heat and helium, and laser stimulation of excess heat. Nuclear emissions from metal deuterides are put forth by several groups. Observations of transmutation, including the Iwamura experiment and others, are also discussed. Updates on theoretical efforts from the different groups are included as well